2013
DOI: 10.1080/09658211.2013.861916
|View full text |Cite
|
Sign up to set email alerts
|

Modelling longitudinal changes in older adults' memory for spoken discourse: Findings from the ACTIVE cohort

Abstract: Episodic memory shows substantial declines with advancing age, but research on longitudinal trajectories of spoken discourse memory (SDM) in older adulthood is limited. Using parallel process latent growth curve models, we examined 10 years of longitudinal data from the no-contact control group (N = 698) of the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) randomized controlled trial in order to test (a) the degree to which SDM declines with advancing age, (b) predictors of these age-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…For example, a meta-analysis by Johnson (2003) revealed that on average, older adults perform at about the 22nd percentile of the distribution of younger adults in text memory. Similar effect sizes for age-related declines in immediate language memory have been found in a longitudinal study tracking changes in older adults’ auditory discourse memory over a 10-year period ( Payne et al, 2014b ). Although there is considerable debate regarding the impact of WM deficits on on-line measures of real-time language processing in aging ( Caplan and Waters, 1999 ; Kemper and Liu, 2007 ; Caplan et al, 2011 ; Payne et al, 2014a ), verbal WM has been found to reliably mediate age-related changes in “off-line” measures of language comprehension and language memory ( Kwong See and Ryan, 1995 ; Van der Linden et al, 1999 ; Hertzog et al, 2003 ; DeDe et al, 2004 ; Stine-Morrow et al, 2008 ; Borella et al, 2011 ).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, a meta-analysis by Johnson (2003) revealed that on average, older adults perform at about the 22nd percentile of the distribution of younger adults in text memory. Similar effect sizes for age-related declines in immediate language memory have been found in a longitudinal study tracking changes in older adults’ auditory discourse memory over a 10-year period ( Payne et al, 2014b ). Although there is considerable debate regarding the impact of WM deficits on on-line measures of real-time language processing in aging ( Caplan and Waters, 1999 ; Kemper and Liu, 2007 ; Caplan et al, 2011 ; Payne et al, 2014a ), verbal WM has been found to reliably mediate age-related changes in “off-line” measures of language comprehension and language memory ( Kwong See and Ryan, 1995 ; Van der Linden et al, 1999 ; Hertzog et al, 2003 ; DeDe et al, 2004 ; Stine-Morrow et al, 2008 ; Borella et al, 2011 ).…”
Section: Introductionsupporting
confidence: 72%
“…Performance on complex span tasks declines with aging (e.g., Bopp and Verhaeghen, 2005 ), as does comprehension and memory for language ( Kemper, 1987 ; DeDe et al, 2004 ; Payne et al, 2014b ). For example, a meta-analysis by Johnson (2003) revealed that on average, older adults perform at about the 22nd percentile of the distribution of younger adults in text memory.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have used an intermediate age group to examine whether age-related deficits are already present in midlife (e.g., Ross et al, 2007 ; Schvartz et al, 2008 ; Humes et al, 2013a ; Helfer and Freyman, 2014 ). More accurate estimates of when the first signs of aging in auditory and cognitive performance become apparent can be derived from cross-sectional studies sampling continuously across the entire adult life span (Bergman et al, 1976 ; Baltes and Lindenberger, 1997 ; Park et al, 2002 ; Salthouse, 2009 ; Füllgrabe, 2013 ) or longitudinal studies (Dubno et al, 2008 ; Payne et al, 2014 ). It is also those studies that will inform us about the shape of the trajectory of the decline throughout adulthood.…”
Section: Summary and General Discussionmentioning
confidence: 99%
“…In addition to modeling cognitive skills and strategies, trainers often provide extensive practice on exemplar problems (with feedback), foster self-efficacy regarding performance, and teach individuals how to apply learned strategies to real-world tasks (Hahn & Lachman, 2015), all of which may alter perceptions of control (Bandura, 1996). It is also feasible that control beliefs can affect both older adults’ willingness to participate in a training program, as well as their level of participation once they are enrolled in the program (e.g., Lachman, 2006; Payne et al, 2012; Windsor & Anstey, 2008). …”
Section: The Modifiability Of Control Beliefs Through Cognitive Intermentioning
confidence: 99%